Efektivitas Antibakteri Air Seduhan Daun Sirih (Piper Betle Linn.) Sebagai Bahan Desinfektan Dengan Metode SemprotTerhadap Pertumbuhan Bakteri Streptococcus Pyogenespada Cetakan Alginat - Caesar, Aya Dini Oase, drg. Ana Riolina, MPH, drg. Suyadi (2015)
Alginate was a hydrocolloid impression material used by dentist on treatment program design, that disinfectant application was important to avoid dentist from spreading infection. Streptococcus pyogenes was a main phatogen bacteria that cause pharyngitis. Spraying is the most secure method that could give minimum distortion on alginate impression. Betel leaf known as an antibacterial herbs. The purpose of this study was to figure out the effectiveness of antibacteria of betel leaf steeping water as sprayed disinfectant against Streptococcus pyogenes growth on alginate impression. Twenty four tube alginates with 10 mm diameter - 15 mm high as sample divided into 6 groups: control groups and groups with 25%, 30%, 35%, 40% and 45% of betel leaf steeping water. All samples were sumerged into Streptococcus pyogenes suspesion for about 10 minutes, and rinsed. Spray material for control group was hydrogen peroxide, while the rest 5 groups were sprayed with betel leaf steeping water, at its each concentration. Samples were then put into vortex mixer, dilution 10-2. The samples then plated in MHA for 24 hours within 37°C incubation. The amount of appeared bacteria were counted. The analysis was held using Kruskall-Wallis and Mann-Whitney. The result showed that betel leaf steeping water with the most significant effect against Streptooccus pyogenes growth on alginate impression was at 30% concentration.